Hubungan Peran Perawat dengan Pemenuhan Kebutuhan Spiritual Pasien di Ruang ICU dan Teratai Rumah Sakit X - Riawati Rosanna; Mira Agusthia; Rachmawaty M.Noer (Pusat riset dan Inovasi Nasional, 2025)
Spiritual services have not been implemented optimally, this is because nurses consider spiritual services less important and not a priority, busyness in the room, differences in religion, considering religion as a private matter, and lack of understanding of spiritual concepts. The purpose of this study was to determine the relationship between the role of nurses and the fulfillment of patients' spiritual needs in the ICU and Teratai Rooms of X Hospital. The research method used was a quantitative research design with a cross-sectional approach, the population in this study was 118 people, and the research instrument used the DSES (Daily Spiritual Experience Scale) spiritual fulfillment questionnaire developed by Underwood and Teresi. The data analysis used was univariate analysis and bivariate analysis. The results of the study showed that the majority of the role of caregiver nurses was sufficient at 56.8% (67 respondents), the majority of patients' spiritual needs were good at 78.8% (93 respondents) and there was no relationship between the role of nurses and the fulfillment of patients' spiritual needs in the ICU and Teratai Rooms of X Hospital with a p-value of 0.630. This research can improve nurse training in spiritual nursing care and provide facilities that support patients' spiritual needs.